Answer:
Explanation:
y = x - 5 ← x - 5 can be subbed for y in the second equation, as shown:
3x - y = 7 → 3x - (x - 5) = 7, or 2x + 5 = 7, or 2x = 2, or x = 1.
Subbing 1 for x in the first equation, we get y = 1 - 5 = -4,
and so the solution is (1, -4).
Second system:
2x + 2y = 12
3x + y = 2
Let's eliminate y first. Mult. the 2nd equation by -2, obtaining:
2x + 2y = 12
-6x - 2y = -4
--------------------
-4x = 8, and so x = -2. Subbing -2 for x in the 2nd equation, we get:
3(-2) + y = 2, or -6 + y = 2, or y = 8
Then the solution to the second system of equations is (-2, 8).